IMIA: Coalescing Medical Informatics Worldwide for 40 Years - Kulikowski, C. A. (Yearbook of Medical Informatics, 2007)
To summarize and highlight the role of IMIA in the past 40 years in becoming the international professional organization that brings together researchers, practitioners, and educators in the field of medical informatics, and more broadly biomedical, nursing, and health informaticsOutlining developments of medical informatics related to IMIA from 1967 to 2007 in a time-line and comparative topic and geographical distribution analyses over selected MEDINFOs from 1980 and selected Yearbooks from 1992 onwards. This illustrates how IMIA, through the global reach of its activities, has helped advance the science and development of informatics across the entire spectrum of biomedical and health care research, education, and practice.The contribution of IMIA over the past 40 years has been to sponsor and coordinate international conferences and promote interchange and collaborations in biomedical and health informatics by linking national and regional societies, organizing meetings, high quality publications, and working groups. These have helped the coalescing of the discipline worldwide, promoting full participation and a broad interdisciplinary scope that fulfills the hopes of the pioneers in the field.
Keywords: International Medical Informatics Association (IMIA) history; medical informatics; health and nursing informatics; world congresses of medical informatics (MEDINFOs); IMIA Yearbook; and Working Groups